Adolescent Attitudes and Motivation in Stunting Prevention Efforts in Leminggir Village, Mojosari District, Mojokerto Regency - Elies Meilinawati SB (Journal of Innovative and Creativity, 2025)
Stunting is another form of growth failure and chronic malnutrition that occurs over a long period of time, this is different from acute malnutrition. The occurrence of stunting in children is caused by, among other things, the health condition of the mother during childbirth and during adolescence. Adolescents are a group that is vulnerable to health problems. One factor that causes stunting is anemia. Therefore, it is necessary to prevent anemia in adolescents, especially adolescent girls, to prevent children who will be born with stunting. One effort that can be done to prevent anemia in adolescent girls so that later children are not born with stunting is by fulfilling good nutrition during adolescence and understanding stunting. The study purpose was to determine whether there is a relationship between attitudes and motivation of adolescents in efforts to prevent stunting during adolescence in Leminggir Village, Mojosari District, Mojokerto Regency.Materials and methods. The design in this study was cross-sectional. The population was all adolescents in Leminggir Village, Mojosari District, Mojokerto Regency, with a simple random sampling technique of 31 people.Results. The data were analyzed using the Spearman Rank test using the SPSS program and the results obtained ρ-value = 0.002 (ρ-value <0.05) so it can be concluded that there is a relationship between attitudes and motivation of adolescents in efforts to prevent stunting during adolescence in Leminggir Village, Mojosari District, Mojokerto Regency.Conclusions. These findings indicate that the more positive attitudes and higher motivation of adolescents, the better their involvement in stunting prevention behaviors, such as fulfilling nutrition, maintaining cleanliness, and awareness regarding reproductive health and future planning. This study emphasizes the importance of empowering adolescents through health education, increasing nutritional understanding, and creating a supportive environment, so as to strengthen their role in efforts to prevent stunting from an early age